âBRIQUETTE LA BENDOâ, PEMANFAATAN LIMBAH AMPAS ONGGOK MENJADI BISNIS BRIKET SEBAGAI PEMBERDAYAAN MASYARAKAT DUSUN BENDO DESA DALEMAN KECAMATAN TULUNG KABUPATEN KLATEN - Pamungkasih, Estri; Cahyono, Muhammad Ridwan Arif; Prisusatyo, Yoga; Yuraida, Yulfa Intan; Karunawardani, Yudia Tirta (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
The development industry in Bendo, Daleman, Tulung, Klaten District is flour processing from Arenga pinnata trees. Beside produces flour, this industry also produces biomass waste in abundant quantity. This waste is not fully utilized, so that gives the negative impact to local air and water quality. UGM students through Student Creativity Program took an initiative to utilize the biomass waste into briquettes together with the local community. The implementation of this activity conducted from February until July 2013. The activities including observation and identification of issues, public education, training briquettes production, society empowerment and the establishment of Small Medium Enterprises. The results show that the community supports the dissemination activities and ready to carry out the activities. The community has been able to make briquettes from beginning till end. However, the community has still not to make briquettes continuously and sustainability. This condition cause the plan to establishment small medium enterprise is delayed. Besides that, this activity has publication by online news and newspaper about utilization of biomass waste into briquettes. Therefore, the community need to empowerment intensively to make briquettes, reparation the briquettes tools in order to effective and efficiently, and then actuating to establishment the Small Medium Enterprises of briquettes. In the future, if this activity is sustainability, it can reduce the amount of biomass wastes in case to improve the air and water quality.